Hubungan Kepercayaan Diri Dan Kecemasan Dengan Perilaku Menyontek Saat Menghadapi Ujian Nasional Pada Siswa Kelas Xii Sman 8 Bekasi - Harwendra S, Moch Aden; J. Silaen, Sondang Maria (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2020)
This research is a quantitative study that aims to examine the relationship of confidence and anxiety with cheating behavior during national examinations in class XII students of SMAN 8 Bekasi. The subjects in this study were 191 students in class XII of SMAN 8 Bekasi as a sample using a proportional sampling technique random sampling. This study uses 3 scales, namely: the Cheating Behavior scale, the Confidence scale, and the HARS scale to measure anxiety. The results of this study indicate that there is a significant relationship between Confidence and Cheating Behavior at SMAN 8 Bekasi with r = 0.750 and p = 0.000 <0.05. There was a significant relationship of anxiety support with cheating behavior r = 0.627 and p = 0.000 <0.05. There is a significant relationship of Confidence and Anxiety with Cheating Behavior R = 0.762 and p = 0.000 <0.05. From the results of the study it can be concluded that the higher the confidence the lower the cheating behavior and vice versa, the lower the confidence the higher the cheating behavior, then the lower the anxiety the lower the cheating behavior, so the higher the anxiety the higher the higher the anxiety cheating behavior